2020
DOI: 10.1182/blood.2019003348
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical effector functions of the T-memory–like T-PLL cell are shaped by cooperative TCL1A and TCR signaling

Abstract: T-cell prolymphocytic leukemia (T-PLL) is a poor-prognostic neoplasm. Differentiation stage and immune-effector functions of the underlying tumor cell are insufficiently characterized. Constitutive activation of the T-cell-leukemia-1A (TCL1A) oncogene distinguishes the (pre)leukemic cell from regular post-thymic T-cells. We assessed here activation-response patterns of the T-PLL lymphocyte and interrogated the modulatory impact by TCL1A. Immunophenotypic and gene expression profiles revealed a unique spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 53 publications
1
36
1
Order By: Relevance
“…Ibrutinib and venetoclax are a pairing which has shown synergy in some 9 , but not all 6 , laboratory investigations with T-PLL samples and with reported tolerability in patients with CLL 17 . Two clinical responses 9 and a period of stable disease halting exponential proliferation in another case 10 have been reported also, and a clinical trial (NCT03873493) is underway to further evaluate this combination in patients with T-PLL. Utilizing a multiagent regimen targeting key pathways in T-PLL, a remarkable response with venetoclax plus alemtuzumab, cladribine, and vorinostat was described in a patient with very active disease and who previously had progressed during venetoclax monotherapy ramp-up 8 .…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Ibrutinib and venetoclax are a pairing which has shown synergy in some 9 , but not all 6 , laboratory investigations with T-PLL samples and with reported tolerability in patients with CLL 17 . Two clinical responses 9 and a period of stable disease halting exponential proliferation in another case 10 have been reported also, and a clinical trial (NCT03873493) is underway to further evaluate this combination in patients with T-PLL. Utilizing a multiagent regimen targeting key pathways in T-PLL, a remarkable response with venetoclax plus alemtuzumab, cladribine, and vorinostat was described in a patient with very active disease and who previously had progressed during venetoclax monotherapy ramp-up 8 .…”
Section: Dear Editormentioning
confidence: 99%
“…Prior studies have reported three patients who achieved partial remission (PR) with venetoclax monotherapy 5,6 and a more durable (10 months) complete response with combination venetoclax and pentostatin 7 . Recently, additional case reports have also suggested superior responses when venetoclax was administered in a combination approach [8][9][10] . Herein, we report outcomes of patients with relapsed/refractory T-PLL treated with venetoclax at our institution.…”
Section: Dear Editormentioning
confidence: 99%
“…The expression of TCL1A in embryonic tissues, as well as its recurrent overexpression and prognostic/predictive value in different malignancies, implicates an important function of TCL1A in key signaling pathways mediating stemness and survival (Figure 1). [24,26,61]; (E) interaction of the TCL1A homodimer with AKT molecules leads to augmented trans-phosphorylation and catalytic activity of the oncogenic Ser/Thr kinase AKT, resulting in increased survival signaling [62]; (F) the interaction of TCL1A with AP-1 components-namely, JUN, JUNB, and FOS, leads to impaired AP-1 signaling and thereby sustained anti-apoptotic signals [11]; (G) TCL1A interacts with IκB and mediates its phosphorylation via ATM, leading to its subsequent ubiquitination-dependent degradation. Inhibition of this negative regulator IκB causes increased NF-κB signaling, which is additionally strengthened by the TCL1A-p300 interaction [11]; (H) physical interaction of TCL1A with DNMT3A reduces the methyltransferase activity of DNMT3A, which leads to a higher number of hypomethylated genomic regions [63], which is implicated in the pathogenesis of CLL [64].…”
Section: The Physiological and Disease-associated Function Of Tcl1amentioning
confidence: 99%
“…In Tcl1a −/− mice, the bulge cells show reduced expression of the stem cell marker CD34. Furthermore, a Tcl1a knockout led to reduced proliferation of TA cells, needed for new hair formation[59]; (C) upregulation of Tcl1a leads to metabolic shifts toward aerobic glycolysis via activation of Akt and repression of Pnpt1, thereby contributing to pluripotency of induced pluripotent stem cells (iPSCs)[60]; (D) in cells of chronic lymphocytic leukemia (CLL) and T-cell prolymphocytic leukemia (T-PLL), TCL1A increases the responsiveness to B-cell receptor (BCR) and T-cell receptor (TCR) stimulation, respectively, by a kinase activating effect[24,26,61]; (E) interaction of the TCL1A homodimer with AKT molecules leads to augmented trans-phosphorylation and catalytic activity of the oncogenic Ser/Thr kinase AKT, resulting in increased survival signaling[62]; (F) the interaction of TCL1A with AP-1 components-namely, JUN, JUNB, and FOS, leads to impaired AP-1 signaling and thereby sustained anti-apoptotic signals[11]; (G) TCL1A interacts with IκB and mediates its phosphorylation via ATM, leading to its subsequent ubiquitination-dependent degradation. Inhibition of this negative regulator IκB causes increased NF-κB signaling, which is additionally strengthened by the TCL1A-p300 interaction[11]; (H) physical interaction of TCL1A with DNMT3A reduces the methyltransferase activity of DNMT3A, which leads to a higher number of hypomethylated genomic regions[63], which is implicated in the pathogenesis of CLL[64].…”
mentioning
confidence: 99%
“…reported disease stabilization after short-term treatment of one patient with venetoclax plus ibrutinib, but progression after cessation of treatment. 14 Alfayez et al . treated one patient with venetoclax plus pentostatin who achieved complete remission for 10 months.…”
mentioning
confidence: 99%